Synthesis and biological activity evaluation of new isatin-gallate hybrids as antioxidant and anticancer agents (in vitro) and in silico study as anticancer agents and coronavirus inhibitors - May Mohammed Jawad Al-Mudhafar; Jaafar Suhail Wadi (Pensoft Publishers, 2024)
Background: The hybrid compounds hold promise for developing novel pharmaceuticals, potentially exhibiting greater activity, mainly against viruses and cancer diseases, than their components. Objective: In this study, researchers explored the potential synergistic effects of hybrid molecules by designing and synthesizing a series of isatin-gallate hybrids, denoted as N'-(5-substituted-2-oxoindolin-3-ylidene)-3,4,5-trihydroxybenzohydrazide (3a-d). Methods: Isatin-gallate hybrids (3a-d) were synthesized by reacting gallic hydrazide with each of the isatin analogs (2a-d). The structures of all produced compounds were described using spectrum methods such as fourier transform infrared (FTIR), 1H-nuclear magnetic resonance spectroscopy (1H-NMR), and physicochemical attributes. The evaluation of the tested hybrids (3a-d) involved assessing their in vitro antioxidant activities using the α, α-diphenyl-β-picrylhydrazyl (DPPH) free radical scavenging method and cytotoxic activities through the MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] colorimetric assay for measuring cellular growth. Furthermore, in silico analysis was applied to the final hybrids to evaluate their effects as anticancer and anti-coronavirus agents. Conclusion: Among the examined hybrid compounds, 3b demonstrated substantial in vitro antioxidant and cytotoxic activities. In silico analysis revealed slight variations in the anticancer activity of compounds 3a-d, with differing affinities observed across various cancer cell lines. Additionally, these compounds exhibited moderate efficacy in inhibiting coronavirus activity.